Inhibition of osteoclast differentiation by (1→3)-β-D-glucan from Alcaligenes faecalis (curdlan) and dectin-1 interaction via the syk proteolytic system - Wataru Ariyoshi; Ayaka Koga; Yuki Kodama; Ryota Yamasaki; Yoshie Nagai-Yoshioka; Michihiko Usui; Shinichi Mochizuki; Yoshiyuki Adachi (Carbohydrate Polymer Technologies and Applications)
We previously demonstrated that curdlan, a dectin-1 agonist, inhibits osteoclast formation via proteolysis of spleen tyrosine kinase (syk). In this study, we elucidated the molecular mechanism underlying the inhibition of osteoclast differentiation via syk proteolysis upon interaction of curdlan and dectin-1. Pretreatment with bafilomycin A1 or E64d/pepstatin markedly blocked syk degradation induced by curdlan in RAW264.7 cells overexpressing dectin-1 (d-RAW cells). Curdlan stimulation increased autolysosome formation and expression of autophagy marker, LC3-II. These results indicate that autophagy plays an important role in the inhibition of osteoclast formation by curdlan via syk degradation. This notion was supported by increased expression of autophagy-related genes in curdlan-treated d-RAW cells. Moreover, we found that recruitment to early endosome and internalization of curdlan–dectin-1 complex via clathrin-, caveolae- and lipid raft-mediated endocytosis are required for curdlan-induced syk degradation in D-RAW cells. We found that EPS15 may be an important molecule involved in the collaboration between endocytosis and autophagy in the system for syk degradation by curdlan. Overall, these results suggest that the negative regulation of osteoclast differentiation of curdlan via interaction with dectin-1 on the plasma membrane contributes to autophagy-mediated degradation of syk in conjunction with endocytosis.